Poligami Atas Nama Agama: Studi Kasus Kiai Madura - Masthuriyah Sa’dan (UIN Sunan Kalijaga Yogyakarta, 2015)
Having more than one wife for Madurese Kyai is not unusual. In fact, parents would feel proud and happy when their daughters are proposed to be one of the Kyai’s wifes. This discussion exclude the fact of socio economic factors and the low level of knowledge and education among Madurese girls. In this context, some Kyais that served as role models and religious leaders, have taken the benefit through the theological proposition that polygamy is the sunnah of the Prophet and Islam. It is urgent then to reconstruct the paradigms of some kyais and Madurese community. Applying a contemporary socio humanities approach and Feminist Islamic analysis, the article constitutes that polygamy is the result of unfair religious interpretations of gender. In this regard, polygamy is a crime in the form of marriage since polygamy is only for the man’s libido and sexual modus. In other word, polygamy violates women and children’s human rights.[Memiliki istri lebih dari satu bagi kiai Madura bukanlah hal yang tabu. Bahkan, orang tua yang memiliki anak gadis dan dipersunting oleh kiai untuk menjadi istri yang kesekian akan merasa bangga dan bahagia. Terlepas dari faktor sosial ekonomi dan minimnya tingkat pengetahuan dan pendidikan anak-anak perempuan Madura. Kiai sebagai panutan dan tokoh agama telah memanfaatkan perempuan dengan dalil teologis bahwa poligami adalah sunnah Nabi dan ajaran Islam. Untuk itu, merekonstruksi paradigma berpikir kiai dan masyarakat Madura menjadi sangat urgen. Dengan menggunakan pendekatan sosial humanities kontemporer dan analisa Islam feminis, poligami merupakan hasil dari interpretasi keagamaan yang bias gender. Poligami adalah bentuk kejahatan dalam perkawinan. Poligami hanyalah modus libido dan seksual laki-laki dan poligami melanggar hak asasi perempuan dan anak.]